Exploring tourist animosity and its influence on destination choices in the post-covid 19 era : A study of Vietnamese independent travelers - Dang Hung Vu; Pham Tran Truc Vien (My University, 2023)
Exploring tourist animosity and its influence on destination choices in the post-covid 19 era : A study of Vietnamese independent travelers
Keywords: Tourist animosity